Formação de classes de estímulos equivalentes auditivos e táteis por crianças com deficiência visual - Canosa, Alessandra Corne (2013)
The study of the model of stimulus equivalence has contributed to understanding the emergence of new behaviors, as well as widely used as a model for the study of symbolic behavior. The research has privileged the use of auditory and visual stimuli on the study of learning for a population of participants with intellectual disabilities or deafness, with scarce records of studies conducted with participants with visual impairments. This experimental study investigated the formation of equivalence classes using auditory and tactile stimulus. Participated three 5 years old children with vision impairments and typical development. The stimuli used were three different animals, presented in two ways. Tactile stimuli were plush animals with sizes proportional to each other (B) and raised drawing (D), and the auditory were the dictated animals names (A) and the replica of the sounds produced by animals (C). For the test of generalization were used plush animals of the same size (E) and plastic animals toys (F). The participants were exposed to a matching-to-sample procedure to teach relations between the dictated animals names and the plush animal (AB), dictated animals names and the sound produced by the animal (AC) and dictated animals names and raised drawing (AD), to produce the learning of arbitrary conditional relations between stimuli. In this study, the three comparison stimuli were presented since the beginning of the teaching‟s stages. After teaching, we tested the emergence of CB/BC and DB/BD relations, not directly taught, aiming at verifying the formation of classes equivalent stimulus of three (ABC) and four stimulus (ABCD). The results indicated that all participants showed high performance in tests and demonstrated the formation of equivalence classes when used auditory and tactile stimuli. The generalization tests indicated repertoires learned extended to other stimuli. This study can contribute to the development of appropriate teaching procedures for children with visual impairment, as well as to the adequacy of existing methods and resources.